APPLYING THE LESSONS: IDEALS VERSUS REALITIES OF HAPPINESS FROM MEDIEVAL ISLAM TO THE "FOUNDING FATHERS" - Cornell, Vincent J. (Journal of law and religion, 2014)
The idea of happiness and its pursuit have been taken up by thinkers in many times and places. This article examines the role of happiness as a concept and goal in medieval Islamic thought and, especially, in the work of Abū Ḥāmid Muḥammad al-Ghazālī and Abū Naṣr al-Fārābī. In examining Ghazālī's and Fārābī's perspectives on happiness, the article looks at the influence of Plato and Aristotle on these medieval Islamic thinkers and puts Islamic thought on happiness in conversation with the views of the American founders.